2020
DOI: 10.1002/advs.201903307
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric Thymosin β4 Loaded Nanofibrous Interface Enhanced Regeneration of Muscular Artery in Aging Body through Modulating Perivascular Adipose Stem Cell–Macrophage Interaction

Abstract: Regenerating nonthrombotic and compliant artery, especially in the aging body, remains a major surgical challenge, mainly owing to the inadequate knowledge of the major cell sources contributing to arterial regeneration and insufficient bioactivity of delivered peptides in grafts. Ultrathin nanofibrous sheaths stented with biodegrading elastomer present opening channels and reduced material residue, enabling fast cell recruitment and host remodeling, while incorporating peptides offering developmental cues are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…The vascular grafts were composed of PGS core and PCL/collagen nanofibrous sheath as described previously [ 5 ]. In brief, the sodium citrate tubes and the NaCl tubes were instilled with PGS respectively and crosslinked at 150 °C for 24 h to obtain two different PGS cores.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The vascular grafts were composed of PGS core and PCL/collagen nanofibrous sheath as described previously [ 5 ]. In brief, the sodium citrate tubes and the NaCl tubes were instilled with PGS respectively and crosslinked at 150 °C for 24 h to obtain two different PGS cores.…”
Section: Methodsmentioning
confidence: 99%
“…For example, PDGF-BB secreted by anti-inflammatory macrophages can promote the myogenic differentiation of vascular progenitor cells. The crosstalk between macrophages and stem cells plays key role in myogenesis of vascular graft [ 5 ]. The general strategy promoting vascular regeneration involves targeting vascular precursor cells, enhancing endothelialization, and fabricating bioactive biomaterials [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophages, as the key cells in innate immunity, can release multiple molecules modulating in situ endothelialization process [ 277 , 278 ]. It has been reported that TNF-α secreted by macrophages plays a role in regulating migration and differentiation of EPCs and graft development.…”
Section: Immunomodulation In Vascular Graft Developmentmentioning
confidence: 99%